Assessment of simulated aerosol effective radiative forcings in the terrestrial spectrum. Issue 2 (27th January 2017) - Heyn, Irene; Block, Karoline; Mülmenstädt, Johannes; Gryspeerdt, Edward; Kühne, Philipp; Salzmann, Marc; Quaas, Johannes
Abstract: In its fifth assessment report (AR5), the Intergovernmental Panel on Climate Change provides a best estimate of the effective radiative forcing (ERF) due to anthropogenic aerosol at −0.9 W m −2 . This value is considerably weaker than the estimate of −1.2 W m −2 in AR4. A part of the difference can be explained by an offset of +0.2 W m −2 which AR5 added to all published estimates that only considered the solar spectrum, in order to account for adjustments in the terrestrial spectrum. We find that, in the CMIP5 multimodel median, the ERF in the terrestrial spectrum is small, unless microphysical effects on ice‐ and mixed‐phase clouds are parameterized. In the latter case it is large but accompanied by a very strong ERF in the solar spectrum. The total adjustments can be separated into microphysical adjustments (aerosol "effects") and thermodynamic adjustments. Using a kernel technique, we quantify the latter and find that the rapid thermodynamic adjustments of water vapor and temperature profiles are small. Observation‐based constraints on these model results are urgently needed. Key Points: The aerosol forcing in the terrestrial spectrum in models is found to be small or accompanied by a strong solar ERF The adjustments are split into thermodynamic and microphysical adjustments. Thermodynamic adjustments are small in the terrestrial spectrum Modeled ERF differs depending on complexity of parameterized aerosol‐cloud interactions. Less comprehensive models show smaller net forcing